Bermuda Triangle - Donkin, Andrew; Nang ChanYeema (New York, USA DK Publishing Inc., 2000)
Explores the mysteries and legends associated with the Bermuda Triangle, an area in the Atlantic Ocean bounded by Bermuda, Florida, and Puerto Rico, where hundreds of boats and planes have vanished.
Keywords: Level Books